The Psychology of close relationships Fourteen core principles. [article]. - Finkel, Eli J.
Relationship science is a theory-rich discipline, but there have been no attempts to articulate the broader themes or principles that cut across the theories themselves. We have sought to fill that void by reviewing the psychological literature on close relationships, particularly romantic relationships, to extract its core principles. This review reveals 14 principles, which collectively address four central questions: (a) What is a relationship? (b) How do relationships operate? (c) What tendencies do people bring to their relationships? (d) How does the context affect relationships? The 14 principles paint a cohesive and unified picture of romantic relationships that reflects a strong and maturing discipline. However, the principles afford few of the sorts of conflicting predictions that can be especially helpful in fostering novel theory development. We conclude that relationship science is likely to benefit from simultaneous pushes toward both greater integration across theories (to reduce redundancy) and greater emphasis on the circumstances under which existing (or not-yet-developed) principles conflict with one another. -- (from the author)
Keywords: Relationship science; Core principles; Attachment theory; Interdependence theory; Culinary approach